Knocking out USP7 attenuates cardiac fibrosis and endothelial-to-mesenchymal transition by destabilizing SMAD3 in mice with heart failure with preserved ejection fraction - Yuan, Shuai; Wang, Zimu; Yao, Shun; Wang, Yanyan; Xie, Zhonglei; Wang, Jingfeng; Yu, Xueting; Song, Yu; Cui, Xiaotong; Zhou, Jingmin; Ge, Junbo (Theranostics, 2024)
: Heart failure with preserved ejection fraction (HFpEF) is a predominant type of heart failure. Exploring new pathogenesis and identifying potential novel therapeutic targets for HFpEF is of paramount importance. : HFpEF mouse model was established by the "Multiple-hit" strategy, in that 18- to 22-month-old female C57B6/J mice fed with a high-fat diet were further challenged with chronic infusion of Angiotensin II. RNA sequencing analysis showed that USP7 was significantly increased in the heart of HFpEF mice. Liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) analysis, in conjunction with co-immunoprecipitation (Co-IP) techniques, identified expression of SMAD3, the key molecule of endothelial-to-mesenchymal transition (EndMT), was also significantly elevated. USP7 endothelium-specific knockout mice was generated to investigate the involvement of USP7 in HFpEF. The biological significance of the interaction between USP7 and SMAD3 was further explored. : USP7 promotes EndMT and cardiac fibrosis by binding to SMAD3 directly via its UBL (Ubiquitin-like) domain and cysteine at position 223 of USP7, leading SMAD3 deubiquitination to maintain the stability of SMAD3 by removing the K63 ubiquitin chain and preventing the degradation of SMAD3 by proteasomal process. USP7 also promotes SMAD3 phosphorylation and nuclear translocation, thereby aggravating EndMT and cardiac fibrosis. Endothelium-specific USP7 knockout led to improvement of HFpEF phenotypes and reduction of cardiac fibrosis. Overexpression of SMAD3 in endothelium-specific knockout HFpEF mice reversed the protective effects of USP7 knockout in this HFpEF mouse model. Our results indicated that USP7 is one of the key pathogenic molecules of HFpEF, and knocking out USP7 could attenuate HFpEF injury by promoting the degradation of SMAD3. USP7 and SMAD3 inhibition might be potential therapeutic options for HFpEF.